Leaf-trait plasticity and species vulnerability to climate change in a Mongolian steppe - Liancourt, Pierre; Boldgiv, Bazartseren; Song, Daniel S; Spence, Laura A; Helliker, Brent R; Petraitis, Peter S; Casper, Brenda B (Global change biology, 2015)
Climate change is expected to modify plant assemblages in ways that will have major consequences for ecosystem functions. How climate change will affect community composition will depend on how individual species respond, which is likely related to interspecific differences in functional traits. The extraordinary plasticity of some plant traits is typically neglected in assessing how climate change will affect different species. In the Mongolian steppe, we examined whether leaf functional traits under ambient conditions and whether plasticity in these traits under altered climate could explain climate-induced biomass responses in 12 co-occurring plant species. We experimentally created three probable climate change scenarios and used a model selection procedure to determine the set of baseline traits or plasticity values that best explained biomass response. Under all climate change scenarios, plasticity for at least one leaf trait correlated with change in species performance, while functional leaf-trait values in ambient conditions did not. We demonstrate that trait plasticity could play a critical role in vulnerability of species to a rapidly changing environment. Plasticity should be considered when examining how climate change will affect plant performance, species' niche spaces, and ecological processes that depend on plant community composition.
Keywords: Plant Leaves; Grassland; druhová specificita; Mongolian steppe; increased precipitation; Mongolia; Models, Biological; Phenotype; open-top chambers; listy rostlin; biomasa; plasticity; klimatické změny; Mongolsko; warming; climate change; Climate Change; fenotyp; biologické modely; Species Specificity; functional traits; pastviny; Biomass; drought